Islamic Human Resource Management, Organizational Commitment and Employee Performance: A Case Study on Sharia Bank in South Sumatera - Hadjri, Muhammad Ichsan; Perizade, Badia; Marwa, Taufiq; Hanafi, Agustina (International Review of Management and Marketing, 2019)
The study was conducted in South Sumatra, Indonesia, where the percentage of sharia banking assets in South Sumatra is below the average assets of national sharia banking. Research topics on the Islamic Human Resources Management (IHRM) are also very limited in Indonesia, especially in South Sumatra. Most of the research on Islamic Management deals only with Islamic finance and accounting, Islamic marketing, Islamic leadership, Islamic work ethics, gender and management in Islam. This study aims to determine the effect of IHRM on organizational commitment and employee performance. The population in this study were 245 sharia bank employees in South Sumatera, Indonesia, where the respondents were selected 136 by using Slovin formula and proportional stratified random sampling method. The instrument in measuring the variables in this study is the questionnaire distributed to the respondents. The results showed that IHRM consisting of Islamic recruitment and selection variables, Islamic training and Islamic compensation positive and significant impact to organizational commitment and employee performance. Keywords: Islamic Human Resources Management, Organizational Commitment, Employee Performance, Sharia Bank JEL Classification: M12 DOI: https://doi.org/10.32479/irmm.7529